Peningkatan Hasil Belajar Matematika Melalui Pendekatan Teaching at The Right Level Berbantuan Papan Musi - Mursalin, Sulastri; Nilawati Astini, Baik; Triwahyuni, Intan (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
This research aims to improve student learning outcomes in Mathematics subjects using the TaRL (Teaching at The Right Level) approach assisted by Papan Musi media. This approach is an approach based on the level of students' abilities. This learning considers the needs and characteristics of each student. The goal is to create fun learning so that all students can achieve the expected learning goals. The subjects of this study are 32 students (15 male students and 17 female students) of class V. This classroom action research is reflective and collaborative. The implementation is carried out for two cycles. The results of this study show that the application of the TaRl (Teaching at The Right Level) approach assisted by a prayer board can improve the learning outcomes of Mathematics students in grade V of elementary school. This can be seen from the increase in the percentage of the average value of the observation results in cycle 1, namely the completeness value of 51% and the average value of 73%. Of the 32 students, 17 students have achieved KKM scores. There was also a very good increase in cycle 2 with a percentage of 85% and the average score in this cycle reached 87.5%. There were 28 students who improved their learning outcomes. So, using the Teaching at The Right Level learning approach with the help of the musi board media in Mathematics learning has an impact on improving the learning outcomes of grade V students of SDN 1 Mataram.